2006
DOI: 10.1007/s10162-006-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Stereological Estimation of the Spiral Ligament and Stria Vascularis Volumes in Aging and Ménière’s Disease Using Archival Human Temporal Bones

Abstract: The present study applies the unbiased stereological technique-Cavalieri principle to measure the volumes of the stria vascularis (SV) and the spiral ligament (SL) using postmortem archival human temporal bones from normal young and older subjects and subjects with Ménière_s disease. Normative data was obtained from subjects without ages ranging from 15 to 84 years old who had no history of audiovestibular disease (N = 25). For comparison purposes, the normative specimens were divided into three groups: group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Similar alterations of the scala media that resulted in deafness were reported in mice lacking the Kir4.1 potassium channel subunit of the strial intermediate cells (Rozengurt et al 2003) and the NKCC1 co-transporter of the strial marginal cells (Flagella et al 1999). Thus, deafness in head bobber is likely due to the absence of a functional stria vascularis, which is indispensable for the generation and maintenance of the endocochlear potential, and its dysfunction results in hearing deficiencies in rodent models (Ohlemiller 2009) and in humans (Boulay et al 2009;Ishiyama et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Similar alterations of the scala media that resulted in deafness were reported in mice lacking the Kir4.1 potassium channel subunit of the strial intermediate cells (Rozengurt et al 2003) and the NKCC1 co-transporter of the strial marginal cells (Flagella et al 1999). Thus, deafness in head bobber is likely due to the absence of a functional stria vascularis, which is indispensable for the generation and maintenance of the endocochlear potential, and its dysfunction results in hearing deficiencies in rodent models (Ohlemiller 2009) and in humans (Boulay et al 2009;Ishiyama et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…11F). Strial thinning with age is commonly described in humans and animals (Kusunoki et al 2004;Suzuki et al 2006;Ishiyama et al 2007), and may reflect cell changes that lead to EP decline ). Both CBA/J and CBA/CaJ showed significant strial thinning throughout most of the cochlea (Fig.…”
Section: Figmentioning
confidence: 99%
“…Strial thinning is a commonly reported aspect of cochlear aging (Kusunoki et al 2004;Suzuki et al 2006;Ishiyama et al 2007), although it is often not clear when thinning is functionally meaningful. However, differences in strial thickness in our material (Fig.…”
Section: Strial Thicknessmentioning
confidence: 99%
See 2 more Smart Citations